2013
DOI: 10.1021/bc300621n
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Cell Surface Glycosylation in Vivo Using “Double Click” Chemistry

Abstract: Dynamic alterations in cell surface glycosylation occur in numerous biological processes that involve cell–cell communication and cell migration. We report here imaging of cell surface glycosylation in live mice using double click chemistry. Cell surface glycans were metabolically labeled using peracetylated azido-labeled N-acetylgalactosamine and then reacted, in the first click reaction, with either a cyclooctyne, in a Huisgen [3 + 2] cycloaddition, or with a Staudinger phosphine, via Staudinger ligation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 35 publications
2
78
0
5
Order By: Relevance
“…[16] Furthermore, several studies across different classes of fluorophores have shown that the pyridazine products resulting from alkyne-tetrazine cycloadditions are brighter than the dihydropyridazine products resulting from alkene-tetrazine cycloadditions. [9,17] Aside from its beneficial attributes, cyclooctyne has a liability as a chemical reporter: It is large relative to a monosaccharide substrate, unlike azides and terminal alkynes, the more common chemical reporters for glycan imaging. Indeed, unnatural monosaccharides containing modifications larger than a few atoms are generally poor substrates for the biosynthetic enzymes that enable their incorporation into glycans.…”
mentioning
confidence: 99%
“…[16] Furthermore, several studies across different classes of fluorophores have shown that the pyridazine products resulting from alkyne-tetrazine cycloadditions are brighter than the dihydropyridazine products resulting from alkene-tetrazine cycloadditions. [9,17] Aside from its beneficial attributes, cyclooctyne has a liability as a chemical reporter: It is large relative to a monosaccharide substrate, unlike azides and terminal alkynes, the more common chemical reporters for glycan imaging. Indeed, unnatural monosaccharides containing modifications larger than a few atoms are generally poor substrates for the biosynthetic enzymes that enable their incorporation into glycans.…”
mentioning
confidence: 99%
“…87 The core GalNAc was labeled by feeding cells or animals with per-O-acetylated N-azidoacetylgalactosamine (Ac 4 GalNAz). 28,88 The metabolic labeling of OGlcNAc was achieved by using per-O-acetylated Nazidoacetylgalactosamine (Ac 4 GlcNAz) or (Ac 4 GalNAz). 89 Fucose was labeled by using per-O-acetylated 6-azidofucose (6AzFuc) 90 or per-Oacetylated 6-alkynylfucose (alkynyl fucose).…”
Section: Bio-orthogonal Metabolic Labeling For Carbohydratesmentioning
confidence: 99%
“…In fact, a complete understanding of carbohydrate requires a more comprehensive study of glycoscience, particularly in the spatial distribution and the relationship with other related molecules which are rarely investigated. Recently,°uorescent imaging has been implemented to visualize the glycosylation process and identify the carbohydrate functions in cells or organisms, 27,28 but the detailed distribution of carbohydrates or interactions of glycoconjugates cannot be acquired due to the limitation of imaging resolution. Fortunately, super-resolution°uores-cence imaging with rapid development is a promising valuable tool in the carbohydrate study of cells, because of its predominant resolution at the nanoscale level.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown the use of small molecular probes for imaging glycosylation in vivo, with contrast achieved in tumours and other highly glycosylated tissues. 7 Studying glycosylation remains challenging due to the complexity of the glycome. 2 Metabolic glycan labelling has been a powerful tool for labelling cell surface glycans in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…2 Metabolic glycan labelling has been a powerful tool for labelling cell surface glycans in vitro and in vivo. [7][8][9][10][11] In this method, cells are fed with a non-natural monosaccharide carrying a small, inert chemical reporter group. This monosaccharide is then internalised by the cells and accepted by the biosynthetic machinery of glycoprotein synthesis in the Golgi and Endoplasmic Reticulum (ER).…”
Section: Introductionmentioning
confidence: 99%